Lipid profile and body composition of HIV-1 infected patients treated with highly active antiretroviral therapy - Pontes,L. C. R. (2005)
Highly active antiretroviral therapy (HAART) has been associated with the development of a clinical group and metabolic disorders such as peripheral lipodystrophy syndrome in AIDS. The aim of this study was to analyze the lipid profile, the clinical aspects, and the body composition of HIV-1 infected individuals treated with or without protease inhibitor (PI) during the highly active antiretroviral therapy. In total, 62 individuals were evaluated in this study; 15 healthy individuals (Control Group: CG), 11 HIV-1 infected individuals treated without antiretroviral therapy (Group 1: G1), 14 HIV-1 infected individuals treated with antiretroviral therapy plus protease inhibitor (Group 2: G2), and 22 HIV-1 infected individuals treated with antiretroviral therapy without protease inhibitor (Group 3: G3), mean age 35 years old. The time interval for G2 and G3 was greater than or equal to nine months. Patients receiving HAART with PI had significantly lower viral loads, hypertriglyceridemia, and low HDL levels (p<0.05). There were no differences between groups in relation to the lean body mass percentage obtained by mid-arm muscle circumference adequacy or by bioelectrical impedance. The lower percentage of body fat observed in all the HIV-1 infected patients by antropometric assessment and the decreased tricipital skinfold adequacy in the group treated with PI in relation to CG may suggest lipodystrophy in the upper limbs, especially on those treated with PI.